Microglia: Synaptic modulator in autism spectrum disorder - Hu, Cong; Li, Heli; Li, Jinhui; Luo, Xiaoping; Hao, Yan (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by variable impairment of social communication and repetitive behaviors, highly restricted interests, and/or sensory behaviors beginning early in life. Many individuals with ASD have dysfunction of microglia, which may be closely related to neuroinflammation, making microglia play an important role in the pathogenesis of ASD. Mounting evidence indicates that microglia, the resident immune cells of the brain, are required for proper brain function, especially on the maintenance of neuronal circuitry and control of behavior. Dysfunction of microglia will ultimately affect the neural function in a variety of ways, including the formation of synapses and alteration of excitatory-inhibitory balance. In this review, we provide an overview of how microglia actively interact with neurons in physiological conditions and modulate the fate and functions of synapses. We put a spotlight on the multi-dimensional neurodevelopmental roles of microglia, especially in the essential influence of synapses, and discuss how microglia are currently thought to influence ASD progression.